Structural Model of the Influence of Corporate Fundamental Factors on Market Value: A SEM-PLS Approach on LQ45 Companies - Sadikin, Taufik (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2025)
Market value reflects investor perceptions of a firm’s financial condition and future prospects. However, in emerging markets like Indonesia, discrepancies often occur between strong financial fundamentals and actual market valuation. This study aims to develop a structural model that analyzes the influence of fundamental financial factors on market value, with Return on Assets (ROA) as a mediating variable. The research was conducted on 15 companies, consisting of both non-financial and banking firms, consistently listed in the LQ45 Index during the 2021–2023 period. Secondary data were collected from audited financial statements and analyzed using a quantitative approach through Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that CAPEX, DER, FATA, SIZE, and WCTO simultaneously affect ROA with an R² value of 0.577. Partially, CAPEX has a significant positive effect, while SIZE and WCTO show significant negative effects on ROA. DER and FATA are not statistically significant. Furthermore, ROA positively affects PBV; however, it only explains 2.2% of the variance (R² = 0.022). These findings suggest that market value is not solely driven by internal performance, highlighting the importance of incorporating external and qualitative factors in future valuation models.